Development of soft commodity derivative market in function of the risk management in CEE - Vlado Kovacevic; Jonel Subic; Irena Janković (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
This aim of this paper is to analyse possibilities and potential effects of soft commodity derivative market on the development of risk management practice within the CEE. Agricultural producers and other participants in the soft commodity market in CEE are lacking local commodity market. As a consequence, they are relying on hedging strategies on remote derivative markets that results in basis risk. The local soft commodity derivative market with delivery in CEE ports could significantly improve the risk management practice. One of the most important barriers in developing commodity derivatives market is market liquidity. Joint commodity market between different commodity exchanges in the CEE could lead to increase of necessary liquidity. Attempts to develop commodity derivative markets in individual countries within the region were proven to be inefficient lacking the volume of trade. Methodology used in this paper is based on relevant literature review, consultation with experts in commodity trade and market participants and descriptive statistics applied in order to determine grain price volatility. Results of the research indicate that grain price volatility is high causing the need for application of hedging strategies at the commodity exchanges markets. Second, new EU common regulative is providing improved framework for joint commodity exchange clearing by single clearinghouse. Established market with delivery on Black See ports is of special importance for regional stakeholders.
Keywords: Q02; Q14; G23; 330; derivative commodity exchanges; hedging strategies; commodity market; futures contract; basis risk